2015
DOI: 10.1016/j.ausmj.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Construal in Resisting Tobacco Smoking

Abstract: We interpreted depth interviews and personal observations of 29 Tongan and New Zealand European (NZE) women who self-identified as non-smokers to examine the role of self-construal in the creation and maintenance of their smoking-resistant identities. Our research offers substantive contributions to the smoking prevention literature because most prior work has been situated wholly within Western cultural contexts. We contribute methodologically by showing how a multicultural team-based approach can reap the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example, RISC scale allows a better understanding of behaviours such as communication (e.g. Singelis & Brown, 1995), conflict management (e.g., Lu, Fung, & Doosje, 2017), social relationships and relationships within social networks such as Facebook (Chang, 2015) and even addiction behaviours such as tobacco consumption (Fifita, Smith, & Fernandez, 2015) or financial and social risk taking (e.g., Mandel, 2003). Relational interdependent self-construal is an important dimension of gender differences (Maddux & Brewer, 2005;Kashima et al, 1995) and is useful, for example, for understanding social-evaluative concerns (Russel, Gould, & Fergus, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, RISC scale allows a better understanding of behaviours such as communication (e.g. Singelis & Brown, 1995), conflict management (e.g., Lu, Fung, & Doosje, 2017), social relationships and relationships within social networks such as Facebook (Chang, 2015) and even addiction behaviours such as tobacco consumption (Fifita, Smith, & Fernandez, 2015) or financial and social risk taking (e.g., Mandel, 2003). Relational interdependent self-construal is an important dimension of gender differences (Maddux & Brewer, 2005;Kashima et al, 1995) and is useful, for example, for understanding social-evaluative concerns (Russel, Gould, & Fergus, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing recognition that hope plays a significant role in improving people's wellbeing, with evidence that hope is effective in dealing with emotional exhaustion (Sherwin et al, 1992), engagement in healthy behavior and resolution (Berg et al, 2011). Other research demonstrates that hope has a positive relationship with people's mental health (Kwon, 2000), overall satisfaction (Adams et al, 2002; Luthans and Jensen, 2002; Taylor and Brown, 1988), self-efficacy, optimism and individual performance (Feldman and Kubota, 2015), workplace behaviors (Adams et al, 2002), and dispositional mindfulness and wellbeing (Malinowski and Lim, 2015). Furthermore, Youssef and Luthans (2007) have found that hope supports and sustains the resilience to overcome adversity and strengthens effectiveness in achieving difficult goals.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…But a close examination of recent issues of this journal will reveal the journal also publishes work related to transformative consumer research (e.g. Fifita et al, 2015) as well as specific topics of interest to multiple disciplines. Examples of these are digital marketing (de Ruyter et al, 2018) and customer engagement (Abdul-Ghani et al, 2019).…”
Section: Positioning Theoreticallymentioning
confidence: 99%